Genetic consequences of pond production of a pikeperch (Sander lucioperca L.) stock with natural origin: the effects of changed selection pressure and reduced population size - Tamás Molnár; Ildikó Benedek; Balázs Kovács; Attila Zsolnai; István Lehoczky (PeerJ, 2020)
The pikeperch (Sander lucioperca L.) possesses great potential for diversifying European aquaculture. However, studies on the genetic risk of stocking natural waters with farmed individuals of this species have been limited. Even the effect of pond culture on the genetic composition of stocks with natural-origin has not yet been determined. Our study aimed to compare the genetic variability of a wild living pikeperch population, a pond cultured broodstock (originating from the wild population) and its offspring generation. We also aimed to detect the potential signs of selection using three different methods. By analyzing the molecular data with 14 microsatellite markers, we illustrated that the impact of pond culture on the genetic diversity of fish stocks is similar to hatchery rearing due to its diversity reducing effect caused by using lower effective population sizes. Although the heterozygosity was similar in all populations (Ho = 0.68–0.71), the average number of alleles and allelic richness were significantly lower in the pond cultured stocks (NA = 7.5 and 6; AR = 7.5 and 5.9) compared to the wild population (NA = 11.00, AR = 10.47). Despite the semi-natural conditions of the present study, we detected changing selection pressure in one of the 14 microsatellite markers.